AromaDb: A Database of Medicinal and Aromatic Plant’s Aroma Molecules With Phytochemistry and Therapeutic Potentials - Kumar, Yogesh; Prakash, Om; Tripathi, Himanshu; Tandon, Sudeep; Gupta, Madan M.; Rahman, Laiq-Ur; Lal, Raj K.; Semwal, Manoj; Darokar, Mahendra Pandurang; Khan, Feroz (Frontiers in Plant Science, 2018)
In traditional, herbal medicine, and aromatherapy, use of essential oils and their aroma compounds have been known since long, for the management of various human diseases. The essential oil is a mixture of highly complex, naturally occurring volatile aroma compounds synthesized by medicinal and aromatic plants as secondary metabolites. Essential oils widely used in pharmaceutical, cosmetic, sanitary, food industry and agriculture for their antibacterial, antiviral, antifungal, antiparasitic, insecticidal, anticancer, neuroprotective, psychophysiological, and anti-aging activities. Moreover, volatile aroma compounds comprise a chemically diverse class of low molecular weight organic compounds with significant vapor pressure. However, aroma compounds produced by plants, mainly attract pollinators, seed dispersers and provide defense against pests or pathogens. However, in humans, about 300 active olfactory receptor genes are involved to detect thousands of different aroma compounds and modulates expression of different metabolic genes regulating human psychophysiological activity, brain function, pharmacological signaling, and therapeutic potential. Keeping in mind this importance, present database, namely, AromaDb (http://bioinfo.cimap.res.in/aromadb/) covers information of plant varieties/chemotypes, essential oils, chemical constituents, GC-MS profile, yield variations due to agro-morphological parameters, trade data, aroma compounds, fragrance type, and bioactivity details. The database includes 1,321 aroma chemical structures, bioactivities of essential oil/aroma compounds, 357 fragrance type, 166 commercially used plants, and their high yielding 148 varieties/chemotypes. Also includes calculated cheminformatics properties related to identification, physico-chemical properties, pharmacokinetics, toxicological, and ecological information. Also comprises interacted human genes affecting various diseases related cell signaling pathways correlating the use of aromatherapy. This database could be a useful resource to the plant’s growers/producers, an aroma/fragrance industrialist, health professionals, and researchers exploring the potential of essential oils and aroma compounds in the development of novel formulations against human diseases.